The monumental landscape transformation of the Island of Babeldaob (Republic of Palau): 3D-documentation and geoarchaeological investigations - Kühlem, Annette; Bork, Hans-Rudolf; Hartl-Reiter, Christian; Tellei, Julita; Vogt, Burkhard; Mieth, Andreas (Journal of Global Archaeology, 2022)
Babeldaob is the largest island of Palau. The landscape of this mostly volcanic island is dominated by monumental earthworks, like terraced hills, crown and moat constructions, and modified ridgelines. The majority of the Palau earthworks were built between 2400 and 1200 BP, making them the oldest examples of monumentality in Oceania according to the current state of research. Despite the degree of landscape transformation on Babeldaob, the monumental aspect of the earthworks, and the fact that oral traditions are of utmost importance in the Palauan society, little information about the construction, the function, and significance of them has been passed down. Notwithstanding several archaeological investigations in the last years, questions about the chronology, genesis, function, and use of the earthworks are still open. Did the terraces serve as settlement areas? Have they been used for horticulture? Did they have a ritual or political significance? Or were they used for defence? Using aerial photogrammetry, we generated 3D-models of 14 earthworks that served as a basis for placing test trenches to investigate the construction methods and function of the monuments. Detailed geoarchaeological, geomorphological, pedological, and sedimentological analysis showed many aspects of building techniques, ancient land use, and the high stability of the earthworks.